The training of the religion teacher - Andrei, Constantin (Technium Social Sciences Journal, 2023)
The most complete knowledge of the situation of the Christian family today and the deeper understanding of its spiritual vocation in the Church and society are imposed as two fundamental coordinates of the teacher of religion. This fact evokes the need for faithfulness and discernment for the faith of every Christian, as well as his need to face the complex reality of today’s society. Respecting the missionary principles of the Church and those of general pedagogy, the religion teacher has several pedagogical roles. The continuous formation of educators who teach religion in schools foresees a necessary and mandatory missionary involvement of the Church.